Confirmation of Ogden syndrome as an X‐linked recessive fatal disorder due to a recurrent NAA10 variant and review of the literature. Issue 8 (1st June 2021) - Gogoll, Laura; Steindl, Katharina; Joset, Pascal; Zweier, Markus; Baumer, Alessandra; Gerth‐Kahlert, Christina; Tutschek, Boris; Rauch, Anita
Abstract: Ogden syndrome is a rare lethal X‐linked recessive disorder caused by a recurrent missense variant (Ser37Pro) in the NAA10 gene, encoding the catalytic subunit of the N‐terminal acetyltransferase A complex (NatA). So far eight boys of two different families have been described in the literature, all presenting the distinctive and recognizable phenotype, which includes mostly postnatal growth retardation, global severe developmental delay, characteristic craniofacial features, and structural cardiac anomalies and/or arrhythmias. Here, we report the ninth case of Ogden syndrome with an independent recurrence of the Ser37Pro variant. We were able to follow the clinical course of the affected boy and delineate the evolving phenotype from his birth until his unfortunate death at 7 months. We could confirm the associated phenotype as well as the natural history of this severe disease. By describing new presenting features, we are further expanding the clinical spectrum associated with Ogden syndrome and review other phenotypes associated with NAA10 variants.